2018
DOI: 10.1021/acschemneuro.8b00134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N,N-Dimethyltryptamine on Rat Behaviors Relevant to Anxiety and Depression

Abstract: Depression and anxiety disorders are debilitating diseases resulting in substantial economic costs to society. Traditional antidepressants often take weeks to months to positively affect mood and are ineffective for about 30% of the population. Alternatives, such as ketamine, a dissociative anesthetic capable of producing hallucinations, and the psychoactive tisane ayahuasca, have shown great promise due to their fast-acting nature and effectiveness in treatment-resistant populations. Here, we investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
154
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(171 citation statements)
references
References 79 publications
11
154
1
5
Order By: Relevance
“…First, psilocybin has cue-potentiated fear on the first extinction trial, and DMT has shown post-acute anxiogenic effects. However, both substances have been shown to generally facilitate the extinction of fear conditioned by a cue, but not by context, which may have been mediated by its action on the amygdala [60,61]. This two-way effect is consistent with the observation that the effects of psychedelics in humans are heavily dependent on the context in which they are used.…”
Section: Animal Studiessupporting
confidence: 78%
“…First, psilocybin has cue-potentiated fear on the first extinction trial, and DMT has shown post-acute anxiogenic effects. However, both substances have been shown to generally facilitate the extinction of fear conditioned by a cue, but not by context, which may have been mediated by its action on the amygdala [60,61]. This two-way effect is consistent with the observation that the effects of psychedelics in humans are heavily dependent on the context in which they are used.…”
Section: Animal Studiessupporting
confidence: 78%
“…According to the published literature, the antidepressant potential of psilocin and psilocybin has not previously been investigated in an animal model of depression. Some studies have reported related effects of serotonergic psychedelics, such as normalisation of learning behaviour by lysergic acid diethylamide in the olfactory bulbectomy model of depression (Buchborn et al, 2014), antidepressant-like effects of N,N-dimethyltryptamine (DMT) (Cameron et al, 2018), and Ayahuasca (Amazonian brew that contains DMT) (Pic-Taylor et al, 2015) in the rodent FST. Other studies have investigated the therapeutic potential of psilocin or psilocybin in animal models of other psychiatric disorders such as anxiety (Horsley et al, 2018), OCD (Sard et al, 2005), and PTSD (Catlow et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…29,33,38 The action of DMT at 5-HT 1A receptors and TAARs affords a rationale for exploring the efficacy of DMT in treating anxiety and depression, and recent rat behavioral models support this hypothesis. 20,39 Moreover, neuroplastic effects linked to antidepressant drug activity (increases in dendritic spine formation, changes in spine morphology, increased synapse formation), as well as neuroprotective, immunosuppressive, anti-ischemic, and anti-inflammatory responses, have been associated with the action of DMT and its congener 5-MeO-DMT at sigma-1 receptors. [40][41][42][43] It has been suggested that cross-talk among serotonin receptors, sigma-1 receptors, and toll-like receptors may underlie common immunomodulatory effects of psychedelic agents.…”
Section: Pharmacologymentioning
confidence: 99%
“…The 13 C resonances are in close agreement with previously reported 13 C peak values. 37,39,53,65,75,76 Figure S5). 54…”
Section: Synthesesmentioning
confidence: 99%